2011
DOI: 10.1002/ibd.21432
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic targets in ulcerative colitis: The importance of ion transporters in the human colon

Abstract: Background: The absorption of water and ions (especially Na+ and Cl−) is an important function of colonic epithelial cells in both physiological and pathophysiological conditions. Despite the comprehensive animal studies, there are only scarce available data on the ion transporter activities of the normal and inflamed human colon. Methods: In this study, 128 healthy controls and 69 patients suffering from ulcerative colitis (UC) were involved. We investigated the expressional and functional characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 60 publications
4
83
1
Order By: Relevance
“…The measurement of the ion transporter activites revealed that in the D group the activities of NHE1-3 isoforms were markedly lower, compared to the control group. This inhibitory pattern is clearly different from our previous observations in ulcerative colitis patients, where the activity of NHE1 was increased, whereas the activity of NHE3 was significantly decreased in colonic epithelial cell [9]. Moreover the activity of CBE was significantly diminished in patients in group D as well.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The measurement of the ion transporter activites revealed that in the D group the activities of NHE1-3 isoforms were markedly lower, compared to the control group. This inhibitory pattern is clearly different from our previous observations in ulcerative colitis patients, where the activity of NHE1 was increased, whereas the activity of NHE3 was significantly decreased in colonic epithelial cell [9]. Moreover the activity of CBE was significantly diminished in patients in group D as well.…”
Section: Discussioncontrasting
confidence: 99%
“…Mutation of this transporter results in congenital chloride-losing diarrhoea [19], moreover, similar conditions develop in SLC26A3-deficient mice [36]. The fact that impaired activities of these transporters were observed in diarrhoea-associated diseases, such as ulcerative colitis and secretory diarrhoea [8,28,50], further underlies the importance of the NHE3 and SLC26A3 in colonic electrolyte and water absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The intestine functions as a secretory and absorptive organ maintaining the homeostatic control of electrolytes and fluid balance that impact on mucosal defenses and the characteristics of the intestinal microbiota (16,17). Intestinal secretion mainly results from the active transport of Cl − and HCO 3 − (46).…”
Section: Hf Diet Alters the Functional Integrity Of The Ileum Via Cftmentioning
confidence: 99%
“…Other elements of epithelial barrier capacity comprise tight junctions (9,10) and production/secretion of antimicrobial peptides (AMP) (11,12). The antibacterial lectin Reg3γ promotes the spatial segregation of microbiota and host in the intestine (13), the secretion and organization of the mucus layer that provides physico-chemical protection and a matrix for secreted antimicrobial molecules (14,15), and the control of electrolyte balance (16,17) contribute to this defense. The microbiota itself participates in strengthening mucosal defenses by stimulating epithelial renewal (18)(19)(20), production of AMP (21), cytoprotection against xenobiotics (22,23), immune maturation, increase of intestinal impermeability (24), and modulation of mucus quality and penetrability (25).…”
mentioning
confidence: 99%
“…A recent study in ulcerative colitis patients reported reduced Cl Ϫ /HCO 3 Ϫ exchange activity in surface colonocytes and a decrease in DRA expression in inflamed biopsies taken from distal colonic segments. 138) These findings provide the molecular explanation for early data demonstrating reduced HCO 3 Ϫ secretion rates in subjects with ulcerative colitis. 134) Both in UC patient biopsies as well as the mouse colon, NHE3 expression was preserved, which is in agreement with another study of unaltered NHE3 expression, but changes in its regulation with respect to PDZ adapter proteins in UC patient biopsies.…”
Section: Distal Colonmentioning
confidence: 66%